Facial Aesthetic Outcomes of Cleft Surgery: Assessment of Discrete Lip and Nose Images Compared with Digital Symmetry Analysis. Issue 4 (October 2016) - Deall, Ciara E.; Kornmann, Nirvana S. S.; Bella, Husam; Wallis, Katy L.; Hardwicke, Joseph T.; Su, Ting-Li; Richard, Bruce M.
Abstract : Background: High-quality aesthetic outcomes are of paramount importance to children growing up after cleft lip and palate surgery. Establishing a validated and reliable assessment tool for cleft professionals and families will facilitate cleft units, surgeons, techniques, and protocols to be audited and compared with greater confidence. This study used exemplar images across a five-point aesthetic scale, identified in a pilot project, to score lips and noses as separate units and compared these human scores with computer-based SymNose symmetry scores. Methods: Forty-five assessors (17 cleft surgeons nationally and 28 other cleft professionals from the UK South West Tri-centre units), scored 25 standardized photographs, uploaded randomly onto a Web-based platform, twice. Each photograph was shown in three forms: lip and nose together, and separately cropped images of nose only and lip only. The same images were analyzed using the SymNose software program. Results: Scoring lips gave the best intrarater and interrater reliabilities. Nose scores were more variable. Lip scoring associated most closely with the whole-image score. SymNose ranking of the lip images related highly to the same ranking by humans ( p = 0.001). The exemplar images maintained their established previous ranking. Conclusions: Images illustrating the aesthetic outcome grades are confirmed. The lip score is reliable and seems to dominate in the whole-image score. Noses are much harder to score reliably. It appears that SymNose can score lip images very effectively by symmetry. Further use of SymNose will be investigated, and families of children with cleft will trial the scoring system. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.